2020
DOI: 10.1038/s41598-020-60762-4
|View full text |Cite
|
Sign up to set email alerts
|

Sea-Level Rise Induced Multi-Mechanism Flooding and Contribution to Urban Infrastructure Failure

Abstract: Sea-level rise (SLR) induced flooding is often envisioned as solely originating from a direct marine source. This results in alternate sources such as groundwater inundation and storm-drain backflow being overlooked in studies that inform planning. Here a method is developed that identifies flooding extents and infrastructure vulnerabilities that are likely to result from alternate flood sources over coming decades. The method includes simulation of flood scenarios consisting of high-resolution raster datasets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 30 publications
0
70
0
1
Order By: Relevance
“…The Honolulu tide gage record (NOAA; station ID: 1612340) has a semi-diurnal range of 0.58 m with a 1.51 ± 0.21 mm/year (30-year average) rate of local SLR. Models show that nuisance flooding can occur when tides exceed 0.20-0.35 m above the mean higher high water datum (Sweet et al 2014;Thompson et al 2019;Habel et al 2020).…”
Section: Study Sitementioning
confidence: 99%
“…The Honolulu tide gage record (NOAA; station ID: 1612340) has a semi-diurnal range of 0.58 m with a 1.51 ± 0.21 mm/year (30-year average) rate of local SLR. Models show that nuisance flooding can occur when tides exceed 0.20-0.35 m above the mean higher high water datum (Sweet et al 2014;Thompson et al 2019;Habel et al 2020).…”
Section: Study Sitementioning
confidence: 99%
“…For example, storms can cause groundwater salinization [107][108][109][110][111] -especially concerning for low-lying islands with limited freshwater supplies such as the barrier islands along subsiding coasts 112 and Pacific atolls [113][114] -and contribute to coastal flooding 115 . For example, a sea level rise model assessment for urban Honolulu, Hawaii (USA) at the end of the century, found that including groundwater processes doubles the size of the flood-prone area compared to when considering marine inundation alone 116,117 .…”
Section: [H1] Groundwater Impactsmentioning
confidence: 99%
“…Hence, the public perception of increasingly frequent and severe impacts could be skewed by the shifting baselines of normalcy, against which the extremeness and remarkability of a particular event are assessed. However, such news and social media-based assessments of impacts have been shown to deliver comparable results to those using conventional threshold-based (Moore and Obradovich 2020) or modelling (Habel et al 2020;Yagoub et al 2020) approaches. Moore and Obradovich (2020) identi ed some circumstances where ood thresholds derived using social media observations were more representative of the vertical height at which impacts typically associated with minor ood occur, than the actual de ned minor thresholds.…”
Section: Inverlochmentioning
confidence: 99%